FDG PET/CT to Detect Incidental Findings in Patients With Hepatocellular Carcinoma—Additional Benefit for Patients Considered for Liver Transplantation?. (July 2021) - Winkens, Thomas; Rudakoff, William; Rauchfuss, Falk; Malessa, Christina; Settmacher, Utz; Freesmeyer, Martin
Abstract : Purpose: FDG PET/CT has been described for noninvasive grading, detection of extrahepatic spread, and recurrence in hepatocellular carcinoma (HCC). As compared with localized imaging approaches (MRI, ultrasonography), FDG PET/CT not only focuses on the liver, but covers a long field of view from the base of the skull to the thighs, visualizing pathologic findings not related to HCC. The aims of this retrospective study were to (1) describe the frequency of relevant incidental findings on FDG PET/CT in HCC patients, (2) evaluate the impact on treatment strategy in HCC patients considered for liver transplantation, and (3) to discuss the role of FDG PET/CT in patients considered for transplantation in general. Methods: Four hundred thirty-nine FDG PET/CT examinations of 345 HCC patients were screened for incidental findings. The clinical information system was searched for examinations performed after FDG PET/CT and aimed at verification of incidental findings. Of 345 HCC patients, 81 patients were considered for liver transplantation. The impact of incidental findings was recorded separately for this subgroup. Results: One hundred one patients with incidental findings in 439 FDG PET/CT examinations were identified. The incidental findings comprised 22 neoplasms (9 malignant) and 52 inflammations. Liver transplantation was not performed because of an incidental finding on FDG PET/CT in 9 (11.1%) of 81 patients. Conclusions: FDG PET/CT is capable of identifying relevant incidental findings (ie, secondary malignancy, benign tumors, and inflammation) in HCC patients and HCC patients considered for liver transplantation and thus influencing HCC patient management. FDG PET/CT might also be beneficial in patients considered for transplantation of different organs.